Strategi Dan Keberhasilan Penanaman Gereja Bagi Pemuda Kristen Di Era Revolusi Industri 4.0 - Megawati Manullang; Trivena Br Nadeak; Mega Intan Tambunan; Yubilate Chriswell Zebua (Jurnal Pendidikan Agama dan Teologi, 2023)
Technological developments that are currently happening have an impact on church planting, thus with digitalization it makes fulfillment of all aspects of human life, otherwise it will be left behind, and this acceleration is also triggered by the covid-19 virus, while the core problem that will be put forward is what Church Planting Strategy, what is the Success of Church Planting for Christian Youth in the Industrial Revolution 4.0 Era, and seeing the Urgency of Church Planting for Christian Youth in the Industrial Revolution 4.0 Era. The purpose of writing this scientific paper is to put forward strategies and successes for Christian youth to carry out ministry in the era of the industrial revolution 4.0. The research method used is data collection qualitative method. The strategy and success of planting this church also includes the role of the Holy Spirit in every believer so that they continue to fulfill God's call. Therefore, we need Christian youth who open their hearts to serve God, especially in the era of the industrial revolution 4.0.